On Being an Arab Student in the UK: An Autoethnographic Study on the Experiences of Overseas Students in the UK - Awada, Hussein (2008)
This dissertation uses autoethnography to provide a rich illustration of the difficulties that face overseas students in the UK higher educational system. I write several stories to present the key difficulties that I, as an Arab student, faced during my undergraduate and postgraduate studies in England. The focus of the stories is on the social and academic difficulties that result from the differences in my home and host countries cultural values and educational systems. The main aim of the dissertation, therefore, is to benefit UK universities and students aiming to pursue their higher degree education abroad, particularly in the UK. For these practical benefits, this dissertation contributes to literature by enriching the predictable problems that are covered in literature and demonstrating some hidden difficulties that are faced by overseas students.